(untitled) (The Research of Medical Science Review, 2025)
Objective: To determine the frequency of upstaging and upgrading of non-muscle- invasive bladder cancer (NMIBC) on repeated transurethral resection of bladder tumor (TURBT). Study Design: Cross-sectional study Place & duration of study: Study was conducted at Sindh Institute of Urology & Transplantation from 18th May, 2023 to 1st January, 2025 Methodology: In this cross-sectional study, we included 62 patients with a pathological diagnosis of pTa/T1 urothelial carcinoma of the bladder on initial TURBT who had adequate muscularis propria present in the specimen. The follow-up TURBT (Re- TURBT) was performed 4 to 6 weeks after the initial procedure, allowing for the assessment of any upstaging or upgrading of the NMIBC or early recurrence. Gender, smoking status, hypertension, diabetes mellitus, tumor stage, histological grade, upstaging, and upgrading on repeat resection will be categorical data. This categorical will be repeated in terms of frequency and percentage. Upstaging was classified as occurring when the tumor was determined to be at a stage higher than previous stage. Early recurrence defined as new tumor found on the re-TURBT, despite complete resection on the initial TURBT Results: The baseline study characteristics reveal that the average age of participants is 61.27±7.89 years. Among the study population, 46 patients (74.2%) were male. The average size of the tumors was 4.66±1.255 cm. Tumor upstaging was observed in 22 cases (35.5%). No early recurrence seen in our study population. Conclusion: There is a high frequency of tumor upstaging and upgrading on repeated TURBT in patients of NMIBC. So, all patients after primary TURBT should be advised follow-up TURBT at 4 to 6 weeks, for the assessment of any upstaging or upgrading of the NMIBC.